The situations of athletes in the face of the decision of the IOC to postpone the Olympic Games - Banio, A. (Summer Olympic Games Tokyo 2020 facing the Coronavirus COVID-19 pandemic, 2021)
The situations of athletes in the face of the decision of the IOC to postpone the Olympic Games Abstract For the first time in history, the period between the Olympic Games has lasted more than 4 years. The largest and most prestigious competition in the world did not take place on the set date due to the SARS-CoV-2 pandemic. The coronavirus, causing severe pneumonia, appeared in the city of Wuhan in central China in December and has spread worldwide, killing over almost two and a half million people The decision to postpone he Games, although obvious, raised many economic, social, political, and, most importantly, sports concerns. Following the events of the last year, it is hard to resist the impression that the fate of the most important athletes in the whole situation has been pushed into the background. This text presents the athletes` positions on the IOC`s decision to postpone the Games to 2021 based on their posts on social networks and interviews in the media.